STRATIGRAPHY AND GEOLOGICAL EVENTS AT THE FRASNIAN-FAMENNIAN BOUNDARY IN THE SOUTHERN URALS - Veimarn A.B.; Kononova L.I.; Pravikova N.V.; Tevelev A.V.; Puchkov V.N.; Abramova A.N.; Artyushkova O.V.; Baryshev V.N.; Maslov V.A.; Pazukhin V.N.; Degtyaryov K.E.; Mosejchuk V.M.; et al. (My University, 2004)
Detailed biostratigraphic correlation of the late Frasnian and Famennian sectoins in the South Urals shows that the key global scale events near the boundary of Frasnian and Famennian are clearlyxpressed in combination with important regional scale tectonic events. The maximum regression occured during triangularis zones time, being recorded as common hiatuses. The beginning of specific ultra-potassic mantle volcanism took place durind the linguiformis Zone. Processes of olistostrom deposition, uplift of the Uralian zone, the start of flysch deposition, the exgumation of the high pressure-low temperature Maksiutovo metamorphic complex also took place very close to the Frasnian - Famennian boundary, as the generale regression coincided with active local tectonic movements as the Magnitogorsk island arc collised with East Europian continent. The global scale events at the F- F boundary are connected withactivity of the Late Devonianuperplume, which encompassed a vast areaof the Kazakhstanian, East Europian, Siberian, Gondwana and South Chinese plates.
Keywords: Famennian; Frasnian; Paleozoic::Devonian::Upper::Famennian; Палеозой::Девонская::Верхний::Франский; Палеозой::Девонская::Верхний::Фаменский; Paleozoic::Devonian::Upper::Frasnian